Bats of Bako National Park and Additional Notes on the Rare Partial Albinism in Fawn Roundleaf Bat (Hipposideridae: Hipposideros cervinus) - Nur Mukminah, Naharuddin; Nursyafiqah, Shazali; Rahmat, Libar; Nur Fatin, Karim; Mohd Ridwan, Abd Rahman; Azuan, Roslan; Mohd Isham, Azhar; Mohd Zacaery, Khalik; Faisal Ali, Anwarali Khan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Bat survey was conducted in Bako National Park from 25th to 29th August 2013. A total of 107 individuals from 11 species of bats were recorded. Hipposideros cervinus was recorded as the most abundance species with 51 individuals while Murina suilla and Rhinolophus affinis were the least abundant with one individual each from total captures. This study has added R. affinis as another new species locality record for the national park. This brings up the total bat species known from the park now to 35 species of bats. Interestingly, an individual of H. cervinus with partial albinism was caught during this survey. This single bat was captured on the 27th August 2013 and will be the first albino bat reported in Borneo and possibly Malaysia. This specimen is an adult female that presents high degree of albinism over most of the body but lacking on the upperparts of the body and part of the wings. Detailed description based on 16 external and craniodental measurements are presented herein along with their species identification through genetic analyses. Further research on the genetic structure and behavior of an albino individual may help to identify the possible causes and consequences of albinism to the bats populations.